FECALITH IN THE ILEUM CAUSING INTESTINAL OBSTRUCTION - Ain, Qurrat -ul-; Azhar, Syeda Anam; Baloch, Sumera; Khan, Sohaib Ahmed; Salim, Areeba (Journal of Ayub Medical College Abbottabad, 2016)
Small bowel obstruction is one of the common conditions presenting in surgical wards, however fecalith is one of the rare causes of bowel obstruction. We present here a case of 65 years old lady, who presented with sub-acute intestinal obstruction. In spite of the initial diagnosis being sigmoid volvulus, exploratory laparotomy revealed a focolith in ileum which was retrieved through an enterotomy and primary closure was done. The patient recovered uneventfully. Thus emphasizing the need of through history and workup which steer us to the correct diagnosis.